Halbuy-Now as a marketplace for surplus food supporting a sustainable halal agri-food supply chain through waste minimization - Ash-Shidiqie, Azkia Yasna Nadhratuzzaman; Nayanda, Najwa Putri; Hanim, Fayza Rachmelia Ayunina; Hidayati, Nurul; Zekkour, Hafidha; Casim, Rashdi M. (IPB University, 2024)
HalBuy-Now is a mobile application designed to address food waste and enhance sustainability in the Indonesian agri-food sector. This application connects consumers with halal-certified restaurants offering surplus food at discounted prices. With the growing global demand for halal products and the persistent issue of food waste, HalBuy-Now provides an innovative solution for redistributing surplus food that would otherwise be discarded. The application also promotes sustainable consumption habits, offers cost-saving opportunities for consumers, and supports local food businesses. Through features such as real-time inventory management and location-based ordering, HalBuy-Now effectively minimizes food waste, reduces carbon emissions, and fosters a circular food economy. Additionally, the application empowers consumers to make well-informed purchasing decisions, contributing to the national goals of sustainability, food security, and the promotion of halal-certified products. By combining technology with sustainable agricultural practices, HalBuy-Now plays a key role in advancing Indonesian efforts to reduce food waste while strengthening its position in the global halal food market.